Participating 16th European Society of Clinical Microbiology and Infectious Disease Summer School - Jae Hyeon Park (Annals of Clinical Microbiology, 2018)
The Korean Society of Clinical Microbiology (KSCM) has supported participation in the European Society of Clinical Microbiology and Infectious Disease (ESCMID) Summer School for several years. The school is held every year in Europe for one week and in 2017 was held at the Borstel Research Center, located in Borstel, a small town near Hamburg, Germany. A total of 80 participants from 26 countries attended and included 42.5% (34) males, 57.5% (46) females, and most were residents. The summer school was held for 6 days except for moving time, and there were 29 lectures, 4 small group tutorials, and 80 student presentations. The lecture subject areas included overall topics of clinical microbiology and infectious diseases. Experts from all over Europe gave lectures explaining the basics as well as recent discoveries. Small group tutorials were mainly focused on tuberculosis. Student presentations included active discussions by the students regarding their research subjects or cases. There were also social events such as dinners, visiting museums, cruise ship excursions, and watching outdoor play. Based on personal experience, I recommend young KSCM members attend the ESCMID Summer School because communicating with people from various countries broadens horizons despite a long itinerary and a busy schedule. (Ann Clin Microbiol 2018;21:36-39)